Cartoon Illustrations and Political Communication: A Visual Review of Prabowo's Campaign - Sucipto, Fentisari; Asrinaldi (Institut Seni Indonesia Padangpanjang, 2024)
This research examines the use of cartoon illustrations in the political campaign of the presidential candidate pair Prabowo - Gibran, focusing on visual analysis using the semiotic theory approach of Charles Sanders Peirce. The use of cartoon illustrations depicting cute and adorable characters contrasts with Prabowo's image as a stern and authoritative former military figure. This study aims to understand how visual cartoon elements are used to shape the candidates' identities and influence voters' perceptions. Through qualitative research methods, data were collected through observation, documentation, and content analysis of campaign media. Peirce's semiotic theory was used to analyze the visual signs and messages contained in the cartoon illustrations. The research findings indicate that cartoon illustrations can effectively create engaging visual narratives and can alter public perceptions of the candidates, although there are challenges in aligning the visual image with the candidates' original character. This research contributes significantly to the understanding of the role of visual communication in political campaigns and its strategic implications.